DEVELOPING AN ENGLISH LEARNING APPLICATION BASED ON INFORMATION SYSTEMS TO IMPROVE SPEAKING ABILITY OF LKP BINTANG MULIA STUDENTS - Maulana, Cecep; Hambali, Hambali (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to develop an English learning application based on information systems to improve the speaking skills of LKP Bintang Mulia students. The app features voice recording, pronunciation practice, speaking exercises, and an essay tool to support structured speaking. This development addresses the limited use of technology and reliance on conventional teaching methods at the institution. Thirty students participated in a pre-test and post-test evaluation covering fluency, pronunciation, vocabulary, and confidence. The average score increased from 62.4 to 78.6, with post-test scores of 79.5 (fluency), 78.0 (pronunciation), 77.8 (vocabulary), and 79.1 (confidence). The gain score was 16.2 and the normalized gain was 0.43, indicating medium effectiveness. A paired t-test showed significant improvement (p < 0.001), and the effect size (Cohen’s d = 2.2) indicated a large impact. Student feedback confirmed the app’s usability and effectiveness. These results show that integrating technology through interactive applications can significantly enhance speaking ability in language learning. Keyword: speaking skills; English learning app; information systems; language technology; LKP Bintang Mulia Abstrak: Penelitian ini bertujuan untuk mengembangkan aplikasi pembelajaran bahasa Inggris berbasis sistem informasi untuk meningkatkan keterampilan berbicara siswa LKP Bintang Mulia. Aplikasi ini memiliki fitur rekaman suara, latihan pengucapan, latihan berbicara, dan alat bantu esai untuk mendukung berbicara terstruktur. Pengembangan ini mengatasi keterbatasan penggunaan teknologi dan ketergantungan pada metode pengajaran konvensional di lembaga tersebut. Tiga puluh siswa berpartisipasi dalam evaluasi pra-tes dan pasca-tes yang mencakup kelancaran, pengucapan, kosakata, dan kepercayaan diri. Skor rata-rata meningkat dari 62,4 menjadi 78,6, dengan skor pasca-tes 79,5 (kelancaran), 78,0 (pengucapan), 77,8 (kosakata), dan 79,1 (kepercayaan diri). Skor penguatan adalah 16,2 dan penguatan ternormalisasi adalah 0,43, yang menunjukkan efektivitas sedang. Uji-t berpasangan menunjukkan peningkatan yang signifikan (p < 0,001), dan ukuran efek (Cohen's d = 2,2) menunjukkan dampak yang besar. Umpan balik siswa mengonfirmasi kegunaan dan efektivitas aplikasi. Hasil-hasil ini menunjukkan bahwa mengintegrasikan teknologi melalui aplikasi interaktif dapat meningkatkan kemampuan berbicara secara signifikan dalam pembelajaran bahasa. Kata kunci: keterampilan berbicara; aplikasi pembelajaran bahasa Inggris; sistem informasi; teknologi bahasa; LKP Bintang Mulia